PENGARUH ATRIBUT PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI FAKULTAS EKONOMI UNIVERSITAS SARJANAWIYATA - Muinah Fadhilah; Lusia Tria; Nazala Yogi (JURNAL ILMIAH EDUNOMIKA, 2021)
The objective of the study was to examine the influence between OPPO smartphone Product Attributes and the Word of Mouth of OPPO smartphones on purchasing decisions. The sampling technique in this study was using purposive sampling technique. The object in this study was OPPO smartphone users (students) Yogyakarta with a sample size of 92 respondents. This object is an OPPO smartphone user who accidentally meets the researcher and this object is in accordance with the researchers' criteria to be used as a data source. The testing is done with a hypothesis to determine whether or not an effect of variable X1 and variable X2 on variable Y. The results of this study prove that product attributes do not significantly influence the purchasing decisions. Word of Mouth has a significant effect on purchasing decisions. This proves that there is a simultaneous influence on the Word of Mouth and product attributes on purchasing decisions.